Segmentation as a base for digital marketing strategies in blood service: A cluster analysis for classifying healthy regional subjects - Khomenko, Liliia; Saher, Liudmyla; Letunovska, Nataliia; Jasnikowski, Adam (E3S web of conferences, 2021)
The work aims to analyse the youth by lifestyle and divide it into segments for more effective interaction in advertising campaigns. The object of the study is young people aged from 18 to 35 living in Sumy, Ukraine. It was performed a cluster analysis using the k-means method in the program Statistica 10 to divide into segments. There were selected 5 clusters. The main parameter for segment division is the age and previous experience of donation or its absence. There are also important: types of family, existence of children, the type of employment, the number of far trips for rest. Demographics is important first and, to a lesser extent, lifestyle. For two clusters it is recommended to use the recruitment strategy; for others - retention strategy with aspects considered in this work. The clusters of respondents identified by the authors also provide an opportunity to divide the residents of the study region in relation to the health problems of the location of their residence in relation to life and activities.